Socio-economic and political legal measures to combat extremism and terrorism (Journal of actual problems of jurisprudence, 2019)
The purpose of this paper highlights the need for prevention of extremism and terrorism in the area ofreligion, respecting the principles of secularism, human rights and fundamental positive change in thereligious situation in the country.Keywords: extremism, terrorism, youth, ethno-nationalist interests.